Gender and Age-Specific Differences in the Association of Thyroid Function and Hyperuricemia in Chinese: A Cross-Sectional Study - Ming Yang; Suyan Cao (International Journal of Endocrinology)
Objective. We aimed to explore gender and age-specific influences on the association between thyroid function and hyperuricemia (HUA) in a large Chinese population. Methods. A total of 19,013 individuals (10,563 males and 8,450 females) were recruited. The association between HUA and thyroid function was analyzed by multivariate logistic regression, and the analyses were stratified by gender and age. Thyroid function subgroups were determined in 2 methods including thyroid status and thyroid-stimulating hormone (TSH) quartiles. Results. Overall prevalence of serum uric acid (SUA) and HUA was significantly higher in males, while TSH value and thyroid dysfunction were higher in females. Increasing trends of the TSH level in both genders as well as HUA prevalence in females were found positively along with aging. However, males showed a reduced trend in HUA risk negatively with aging. Our population showed that the risk of developing HUA in hyperthyroidism, normal euthyroidism, mild hypothyroidism, and overt hypothyroidism subgroups had adjusted ORs of 0.634, 1.229, 1.370, and 1.408, respectively, in males. Subjects in females showed a similar increased risk of HUA with ORs of 0.770, 1.198, 1.256, and 1.458, respectively. Similar tendency was observed in TSH quartiles; the above two models showed significantly higher risk of HUA in the high TSH group of males, but not of females. Aging was a significant risk factor for HUA, particularly in older females after adjusting for TSH. Conclusion. The risk of HUA was positively associated with an elevation in TSH levels in both genders irrespective of age, indicating the protective effects of low TSH on HUA. Males with high TSH value were more vulnerable to suffer significant risk of HUA.